Unusual teratological cases in Scarabaeidae (Coleoptera: Scarabaeoidea): two specimens with multiple malformations - Julián Clavijo-Bustos; Miguel Ángel Torres; Jhon Cesar Neita-Moreno (Revista Chilena de Entomología, 2022)
We described two similar teratological cases with multiple malformations and loss of symmetry observed in specimens of Amithao decemguttatus (Waterhouse, 1876) (Scarabaeidae: Cetoniinae) and Megaceras jason (Fabricius, 1775) (Scarabaeidae: Dynastinae) from Colombia.